The Scapular’s Roles in Developing Shoulder Complex Function - Rijal, Rijal (Faculty of Nursing, Universitas Hasanuddin, 2024)
The scapulohumeral anatomy and biomechanics interact to provide adequate mobility, thus the scapula plays various functions in facilitating optimal shoulder complex function (Paine & Voight., 2013). To support shoulder complex function, they argued that the scapula should have a solid foundation for glenohumeral movement facilitated by periscapular muscles to synchronize shoulder movements and develop scapulothoracic joint stability. However, when scapular muscle weakness or dysfunction occurs, then normal scapular posture and mechanics may change and disturb shoulder complex function, which can lead to lower neuromuscular performance and increased risk of glenohumeral joint damage (Kibler., 1998; Paine & Voight., 2013; Voight & Thomson., 2000). Therefore, current perspective will provide a more detailed description of the scapular roles in forming stabilization and supporting complex shoulder movements.